Comparison of resident bird communities in mangrove forest and oil palm plantations in Selangor, Malaysia - Mohamad Amir Hamzah, Aainaa Syazwani (2018)
Oil palm plantations are constantly being trumpeted with the ability to accommodate the lower species richness and diversity of animals, including birds; while mangrove forest is a highly productive ecosystem and accommodates high diversity of flora and fauna communities. Most importantly, mangrove forest is the last refuge habitat for species that have lost its original habitat. Therefore, it is expected that proximity between oil palm plantations with natural forest (in this study are mangroves) will aid in the conservation of bird species in oil palm plantations, thus utilizing this seminatural habitat as a biological conservation area. The aims of this study are to compare the diversity index of resident bird species in adjacent mangrove forest and oil palm plantations; as well as measuring the effectiveness of point count and acoustic sampling methods in estimating the diversity of birds and suggesting the most appropriate method use in both habitats. This study was conducted in Selangor, Malaysia from October 2012 to November 2013. 480 sampling points were established at a distance of at least 200m from each other. Audio recorder was also placed at each sampling point. Bird observation and recording of bird sound were performed simultaneously for 10 minutes at each point. The results registered 5686 individuals and 115 species of birds in these two habitats including 89 residents, 21 migrants, 4 feral and 1 vagrants. Among the 89 resident species, 8 species were threatened; 1 listed under EN and other 7 species were listed under NT. All threatened species were observed in mangrove while only 4 observed in oil palm plantation. Mangrove forests recorded higher species richness and diversity index, as well as density when compared to the adjacent oil palm plantation. However, both habitats shared the same bird species with a relatively high percentage (74% similarities; 66 species) with omnivorous, insectivorous and carnivorous were the three most feeding guilds recorded in both habitats. There was no significant difference in the identification of bird species when using point counts and acoustic sampling at both study sites. However, if researcher has to choose one method to assess birds in oil palm plantation, point counts should be an option, while either point counts or acoustic sampling are appropriate for bird sampling in mangroves habitat. Although mangrove habitats accommodate high bird diversity index, oil palm plantation had also recorded a high number of generalist’s species, some species of water birds and forest-dependent species as well as NT species. Therefore, it can be concluded that the proximity of natural forest to oil palm plantation is very important to aid in assist bird conservation in plantation. Choosing the appropriate sampling method based to the habitat type is also important for comprehensive sampling that can be used for conservation management of species in concerned habitat.